Prout and economic reform in India and the third world - "Batra, Ravi" (Bombay, 1988)
This book covers the following topics Black money: a curse of the third world, India's vast spiritual heritage; The fundamentals of Prout; Prout's economic system; Prout's system of planning; Ananda nagar: A model of proutist planning; The third world debt;Philosophy of history; India's future Glory etc.
Keywords: Economics